Using evidence and operational responses to accelerate gender equality in Kenya - Åsa Torkelsson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Agriculture is a main contributor to pro-poor growth in Africa, but gender inequalities in the sector hold back agricultural growth and affect household welfare negatively. The sector has been characterized by a lack of gender-disaggregated data and patchy gender-integration in policies and operational responses. To remedy this, the World Bank (WB) and the Government of Kenya (GoK) integrated gender in a pronounced way in the design and implementation of the Kenya Agricultural Productivity and Agribusiness Project (KAPAP). A robust gender-disaggregated baseline was established to provide operational guidance as well as inputs for a policy dialogue that aimed to integrate gender in the agriculture sector. This paper uses the recent empirical and practical experiences as the basis for a discussion on the opportunities and challenges of linking foreign aid to local development processes.
Keywords: F63; J16; N57; O19; 330; poverty reduction; agriculture; gender; markets; Kenya